Gathasaptashati: Retelling Intimate history of Ancient Deccan - Sahgal, Smita (Advances in Social Sciences Research Journal, 2019)
A peep into intimate relations through the study of ancient Indian literature is rather rare. Most of the time Sanskrit literature presents a fairly regulated version of reality, bound by societal norms. On the other hand, Gathasaptashati or Sattasai, composed in Maharashtri Prakrit provides us a rare glimpse into the minds of the populace, especially that of the women who state their intimate desires, anguish and deprivations with a sense of abandon and honesty. This may have become possible as the society of ancient Deccan, where these verses were first composed and compiled, was still not fully stratified or complex. Patriarchy had not yet consolidated and did give women a voice which was preserved in the folklore and recalled now and then subsequently. It may be worth exploring these intimate relations by re-reading some verses and studying the context of their composition. Key words: Gathsaptashati, rendezvous, go-between, traveller, love, eroticism, niti